1993
DOI: 10.2307/2526964
|View full text |Cite
|
Sign up to set email alerts
|

Antidumping Policy

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.When an antidumping policy involves the imposition of duties, the threat of antidumping enforcement may alter strategic behavior under imperfect competition. This point is illus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 3 publications
0
35
0
3
Order By: Relevance
“…Various papers (see e.g. Ethier and Fisher, 1987;Fisher, 1992;Leidy and Hoekman, 1990;Reitzes, 1993) have examined how AD protection gives firms incentives to alter their price or output decisions vis-à-vis free trade in order to influence the AD outcome. This may lead to higher or lower welfare depending on the existing market structure.…”
Section: Related Literaturementioning
confidence: 99%
“…Various papers (see e.g. Ethier and Fisher, 1987;Fisher, 1992;Leidy and Hoekman, 1990;Reitzes, 1993) have examined how AD protection gives firms incentives to alter their price or output decisions vis-à-vis free trade in order to influence the AD outcome. This may lead to higher or lower welfare depending on the existing market structure.…”
Section: Related Literaturementioning
confidence: 99%
“…Ethier and Fischer (1987), Fischer (1992) and Reitzes (1993) broaden the focus on strategic behavior by examining oligopoly games involving both a foreign and domestic firm. In the context of the above general model, these papers set n=2 and model the actions as firms setting prices or quantities.…”
Section: The Cost Of the Prospect Of Ad Dutiesmentioning
confidence: 99%
“…We stress the word "may" in the previous sentences because, as Fischer (1992) shows, even these results may be reversed for various games of price or quantities, depending on other market conditions. In addition, a wider variety of outcomes occur if one considers a game in prices with perfectly substitutable goods, as in Reitzes (1993), or if one examines these games when the dumping margin is calculated using a cost-based approach, as analyzed by Fischer (1992).…”
Section: The Cost Of the Prospect Of Ad Dutiesmentioning
confidence: 99%
“…Reitzes (1993) found that the threat of antidumping enforcement may alter strategic behavior under imperfect competition. Firm behavior may be altered by the mere threat of antidumping enforcement (1993).…”
Section: Literature Reviewmentioning
confidence: 99%